Application of Warm Water Foot Soak Therapy for Pregnant Women with Hypertension (HEALTH CARE: JURNAL KESEHATAN, 2025)
Handling of pregnant women with hypertension can be namely with warm water foot soak therapy. This type of research is quantitative using a Quasi Experiment design with a one group pre- test - post-test design approach, checking is carried out every day for 3 consecutive days at the Payung Sekaki Health Center, Pekanbaru City with 15 respondents, The results of the study show that warm water foot soaks can lower blood pressure in pregnant women. The results of this study found that pregnant women with blood pressure >140/90 mmHg in respondents after warm water foot soak therapy decreased, seen from the mean pre-test post-test results, namely on the first day pre-test systolic 142.00 post-test 139.07 pre-test diastolic 90.60 post-test 88.53, then the second day pre-test systolic 132.60 post-test 128.13 pre-test diastolic 86.20 post-test 84.07. And the third day pre-test systolic 125.33 post-test 123.13 pre-test diastolic 82.27 post-test 80.80. The results of the paired T test obtained a p value of 0.000